The Price Premium Induced by Branding: A Health Care Case Study - Markus Kick (Springer Gabler, 2015)
Germany's statutory health insurance (SHI) system has been radically changed in the year 2009 by the introduction of premium equality across all SHI funds. As of today, all funds charge the same price, which is 15.5% of each insurant's gross income. The option to charge additional contributions as a flat, monthly per head amount in case funds cannot cover their costs has only scarcely been used so far. However, research predicts that this current state of premium equality is soon to be changed (PFISTER, 2009, EIBICH et al., 2011). Based on KICK and LITTICH (2011), I conduct a choice-based conjoint experiment and include the new pricing signal of additional contributions. I find that price is not the dominating criterion on the current market, but equally important to voluntary coverage options. Corporate reputation and a provider's brand name lose importance, but are still a major quality signal within consumers' choice decisions. The brand name TK (Technical Health Insurance Fund), as reputational leader, provides additional value for insurants. TK is able to charge up to exteuro1.46 additional contributions from each insurant per month without falling behind their competitors. Compared to the general contribution rate of 15.5% of each insurant's gross income, of course, exteuro1.46 seems rather low. However, the statutory health insurance funds that already charged additional contributions from their members collected between exteuro5 and exteuro16 per month and head. Using this rational reveals that TK is able to charge close to 10% of the additional contribution range simply due to their reputational advantage. Thus, corporate reputation proves to enhance a fund's bargaining position towards its potential insurants, as it allows charging and justifying price premiums. A second empirical study reveals that people lack knowledge about funds' benefit and coverage portfolios and the SHI system in general. Insurants consistently overestimate funds with comparably higher corporate reputation regarding their benefit and coverage details of selected performance categories. Implications for practitioners and policy makers are discussed.
Additional information: Reworking the story for a broad target audience focussed on practitioners. Cf. Kick M. (2015): Selected Essays on Corporate Reputation and Social Media. Springer Gabler, Wiesbaden, https://doi.org/10.1007/978-3-658-08837-8
Keywords: 330; Healthcare; Branding; Corporate Reputation; Signalling